Climate Change Adaptation Strategy of Upland Farmers (Study of Farmers in Dieng Plateau, Banjarnegara Regency) - ,, Turasih; M Kolopaking, Lala (Sodality: Jurnal Sosiologi Pedesaan, 2016)
ABSTRACTClimate change in the Dieng Plateau area is characterized into five local climatic phenomenon: (1) extreme rainfalls, (2) drought in agriculture, (3) hurricans, (4) extreme temperature, and (5) the unpredictable season. Farmers adaptation strategy towards those adverse impacts is identified by occupation of agriculture land. This land occupation also determines access to capital and intensity level of climate change vulnerability. If a farmer household occupies larger lands, so the access to capital is also more and the intensity level of climate change vulnerability becomes lower. On the contrary, smaller lands occupied leaves farmer households with low access to capital and high climate change vulnerability.Keywords: climate change, adaptation strategy, vulnerability, farmer householdABSTRAKPerubahan iklim di Dataran Tinggi Dieng ditandai oleh lima fenomena iklim lokal yaitu: (1) curah hujan yang semakin ekstrem, (2) kekeringan yang melanda pertanian, (3) angin ribut, (4) suhu ekstrem, dan (5) musim yang sulit diprediksi. Strategi adaptasi untuk menghadapi kondisi iklim tersebut dilakukan oleh rumah tangga petani berdasarkan tingkat penguasaannya terhadap lahan pertanian. Luas lahan pertanian yang dikuasai oleh rumah tangga menentukan akses terhadap modal dan intensitas tingkat kerentanan terhadap perubahan iklim. Semakin luas lahan yang dikuasai oleh rumah tangga petani maka nilai akses terhadap modal relatif lebih tinggi dan tingkat kerentanannya terhadap perubahan iklim semakin rendah. Sebaliknya, Semakin luas lahan yang dikuasai oleh rumah tangga petani maka nilai akses terhadap modal akan semakin rendah dan tingkat kerentanannya terhadap perubahan iklim semakin tinggi.Kata kunci: perubahan iklim, strategi adaptasi, kerentanan, rumah tangga petani